Implementation of the child-friendly school program as a manifestation of a culture of peace at SMP Negeri 15 Yogyakarta - Taltsania Elysia Hidayat; Agustina Tri Wijayanti (Universitas Negeri Yogyakarta, 2025)
This study aims to: (1) Describe the implementation process of the Child-Friendly School programs as a manifestation of a culture of peace at SMP Negeri 15 Yogyakarta; (2) Obtain results on the supporting and inhibiting factors in the implementation of Child-Friendly School programs as a manifestation of a culture of peace at SMP Negeri 15 Yogyakarta and alternative solutions. This study uses a qualitative method. In this study, subjects were obtained through the Snowball Sampling technique. The subjects of this study were the Principal, Vice Principal for Curriculum, Social Studies Teacher, and Guidance Counselor. The data collection techniques used observation, interviews, and documentation. As for the validity of the data in this study, it used triangulation techniques. The results indicate that: (1) The implementation of the Child-Friendly School (SRA) program as an embodiment of a culture of peace at SMP Negeri 15 Yogyakarta has been carried out through the stages of planning and implementation, and has generally run optimally in terms of communication, resources, disposition, and bureaucratic structure; (2) The supporting factors include the presence of legal and formal policy frameworks, strong commitment and coordination among teachers, support from parents and the school committee, as well as ongoing teacher professional development through workshops and MGMP. However, several obstacles remain, particularly limited parental understanding and challenges related to student behavior dynamics and peer conflicts. The researcher proposes strengthening the implementation of the SRA program through student integrity pacts, integration of child-friendly values into school rules, student involvement as peer mediators, and digital-based parental education.